2020
DOI: 10.1002/eng2.12234
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of robust fuzzy logic maximum power point tracking based isolated photovoltaic energy system

Abstract: Photovoltaic (PV) energy is highly promising because of its renewable, green, and environment-friendly nature. In this article, the design and analysis of an isolated PV system using a push-pull converter with a fuzzy logic-based maximum power point tracking (MPPT) algorithm is presented. Furthermore, DC-DC converters, along with intelligent controllers fed with MPPT algorithms, are used to ensure the maximum extraction of incident energy. The proposed methodology utilizes fuzzy logic MPPT techniques based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…In previous research, the AI technique has been implemented for the long-term load and PF of electricity conventionally. In [23][24][25][26], a short-term load and PF using an NN fitting tool were used to compute hourly and daily data of weather temperature and electricity load as input features. Furthermore, the generalized-RNN indicates temperature statistics and price signals as input parameters.…”
Section: Related Workmentioning
confidence: 99%
“…In previous research, the AI technique has been implemented for the long-term load and PF of electricity conventionally. In [23][24][25][26], a short-term load and PF using an NN fitting tool were used to compute hourly and daily data of weather temperature and electricity load as input features. Furthermore, the generalized-RNN indicates temperature statistics and price signals as input parameters.…”
Section: Related Workmentioning
confidence: 99%
“…After the analysis of the results obtained from [20], it is observed that this algorithm successfully meets the required design specification of the harmonic eliminator filter. A Fast Transverse Recursive Least Squares (FT-RLS) is proposed for harmonic estimation in [21]. This algorithm helps to calculate the amplitude, frequency, and phase of the power signal that changes over time.…”
Section: Introduction and Related Studiesmentioning
confidence: 99%
“…Various control techniques, such as ANN, fuzzy logic control technique (FLC), an adaptive neuro-fuzzy-based inference system (ANFIS)-based controller maximum power point tracking (MPPT) to extract maximum power from PV-integrated SAPF, with SRRF-based control algorithm for reference current extraction are executed and validated with strong computational engine OPAL-RT 4510 based on field programmable gate array (FPGA) for real-time testing. e performance evaluation and comparison of various control algorithms (for balanced and unbalanced load) based on THD, losses, voltage drop, and pf have been presented along with optimized cost analysis by Kumar and Bansal [14] and Asif et al [15].…”
Section: Introduction and Related Studiesmentioning
confidence: 99%